Pengaruh Gaya Hidup dan Persepsi Kualitas terhadap Keputusan Pembelian Produk Peter Says Denim di Kota Malang - Rianto, Achmad Cahya; Hendrawan, Dimas (Jurnal Ilmiah Mahasiswa FEB, 2014)
Business convection is one kind of business that is quite popular in Indonesia . Business popularity convection caused by two things . First , the products generated by convection in the form of clothing industry is one of the basic human needs , with a great business opportunity that convection has a clear and growing market share rapidly . Secondly , convection became popular because it uses capital is not too large . Clothing needs is paramount in everything concerning the existence of human life lifestyle and perceived quality of the product purchase decision . Lifestyle is a lifestyle with a form of activities, interests and opinions that affect consumer perception . There is a perception in the consumer's perception that evaluates the quality of subjective information to influence consumers' purchasing decisions . This research is a quantitative study which is based on the philosophy of positivism used to examine the population and the particular sample . The purpose of this study was to examine the influence of lifestyle and perceived quality of the product purchase decision Peter Says Denim in Malang . The method used to analyze the data is by using multiple linear regression analysis . Based on the results of the study , the influence of lifestyle and perceived quality on purchase decisions due to the activities, interests and opinions in lifestyle as well as a guarantee , differentiation , price , product line and product innovation on perception of quality that can affect the choice of products , the time of purchase , the amount of goods purchased and the method of payment in the purchase decision . This leads to a product purchase decision Peter Says Denim in Malang has been good . However, the most dominant influence is the perception of quality in the minds of consumers to determine product purchasing decisions Peter Says Denim in Malang Keywords : Lifestyle , perceived quality , purchasing decisions